Laity and Church temporalities: appraisal of a tradition - Nedungatt, George (Dharmaram canonical studies, 2000)
The role of the laity in the Catholic Church is a live issue today. The discussion has various facets in various countries, like the position of woman in the Church or their ordination to the ministerial priesthood. The laitiy's role in the administration of the temporalities of the Church is a hot issue in certain countries. According to the Second Vatican Council the ecclesial mission of the laity is specific and is to be exercised in the secular sphere. If so, is it not the laity that must be competent and responsible to administer the Church's temporal goods like church property and finances? The present work is an attempt to answer this question. The study has been occasioned by the recent developements in the Syro-Malabar Church regarding the role of laypepole in Church administration on the basis of the ancient Thomaschristian system of yógam. While recognising its merits the author discusses its limits in a critical appraisal. Though the work is focussed on the rights exercised by laypeople in the Thomaschristian system of yógam, the questions raised are of general interest. They are therefore addressed to a wider readership.